Implementation of the Grant Policy for Mass Organizations/Religious Institutions in DKI Jakarta - Mohamad Holid; Izzatusholekha Izzatusholekha (PT Mattawang Mediatama Solution, 2024)
In 2022, the DKI Jakarta Provincial Government will allocate grant funds of more than 350 billion rupiah for 131 mass organizations/religious institutions. The aim of the grant funding policy is to strengthen institutions, activity programs and incentives for religious activists so that the mental and spiritual development of Jakarta residents can be realized to support regional government. This research analyzes the implementation of grant funding policies using qualitative methods with a descriptive analytical approach. The results of the research are; Implementation of grant funding policies is carried out in accordance with provisions. Grant funds help operations and activity programs that are beneficial to the community, the recommended amount of grant funds goes through the Evaluation Team's discussion process, intervention from various parties provides convenience, delivery of the LPJ is timely. Outcomes of the grant funding policy has had a positive impact on improving the spiritual mentality of Jakarta residents